2006
DOI: 10.1111/j.1445-5994.2006.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pulmonary embolus using ventilation/perfusion lung scintigraphy: more than 0.5 segment of ventilation/perfusion mismatch is sufficient

Abstract: Using a simplified diagnostic criterion where all studies showing >0.5 segments of V/Q mismatch are regarded as positive and all others as negative, lung scintigraphy, incorporating Tc-99m Technegas ventilation imaging or its equivalent, can achieve a very high diagnostic accuracy for the detection of PE. Using this technique, less than 5% of scans are indeterminate. A simplified, unambiguous approach to reporting is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Therefore it is not surprising that the prevalence of PE in the group of 98 patients who underwent planar scintigraphy was low (9%) and was comparable to that in the population studied by Howarth (13%) 12. In the group of 49 patients who underwent V/Q SPECT the prevalence of PE was similar to that in the PIOPED II study (19%) 17…”
Section: Discussionsupporting
confidence: 54%
“…Therefore it is not surprising that the prevalence of PE in the group of 98 patients who underwent planar scintigraphy was low (9%) and was comparable to that in the population studied by Howarth (13%) 12. In the group of 49 patients who underwent V/Q SPECT the prevalence of PE was similar to that in the PIOPED II study (19%) 17…”
Section: Discussionsupporting
confidence: 54%
“…It has been shown that more than 0.5 segment of V/Q mismatch is sufficient for the diagnosis of PE. 65 The holistic interpretation of V/Q SPECT should be based upon:…”
Section: V/q Patternsmentioning
confidence: 99%
“…The fundamental point is that lobar, segmental or sub-segmental V/P mismatch serves as the basis for confirming a diagnosis of PE among patients with suspected PE. Howarth et al state that: "at least 0.5 of a segment of ventilation/perfusion mismatch is considered diagnostic of PE" (Howarth et al, 2006). This simplified criterion gave the highest combined sensitivity and specificity, observer reproducibility and fewest indeterminate results.…”
Section: Criteria For Acute Pe According the European Guidelinesmentioning
confidence: 99%